Analisis Pengaruh Ethical Identity Index terhadap Kinerja Perbankan Syariah di Indonesia Menggunakan Sharia Conformity and Profitability - Rismayanti, Siti; Djuwarsa, Tjetjep; Mayasari, Ine; Pakpahan, Rosma (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Islamic banking is widely known and in demand among the public. Public trust is needed to improve bank performance. This study examines how EII affects the performance of Islamic banking using SCnP as measured by ROA, ROE, NPM using a panel data regression REM approach with secondary data samples from BUS and BPRS, Bank Age and Bank Size as moderating variables. The results of this study indicate that EII has an insignificant positive effect and also has a significant positive effect on Islamic banking performance. Bank Age has an insignificant positive effect on the performance of Islamic banking. The interaction of EII with Bank Age has a negative and insignificant effect, meaning that Bank Age does not moderate. Bank Size has a significant positive effect on performance. The interaction between EII and Bank Size has a significant negative effect and is insignificant, meaning that Bank Size can moderate or not.